The cytological examination of vaginal smears in dogs - KARAGIANNIDIS (Α. ΚΑΡΑΓΙΑΝΝΙΔΗΣ), A.; TSILIGIANNI (Θ. ΤΣΙΛΙΓΙΑΝΝΗ), Th.; AMARANTIDIS (Ι. ΑΜΑΡΑΝΤΙΔΗΣ), I. (Journal of the Hellenic Veterinary Medical Society, 2018)
The cytological examination of vaginal smears is a simple, quick and inexpensive method for determination of the estrous cycle stage in dogs. Also, the procedure of vaginal smear collection is painless for the animal. Smears are examined under light microscope, after they have been stained by a proper staining method. The results are based on the observation of cytological alterations of the epithelium cells under the influence of ovarian hormones.